Effect of the injection orientation and position on the leakage flow in a honeycomb-tip turbine cascade. (December 2019) - Wang, Yabo; Song, Yanping; Yu, Jianyang; Chen, Fu
Highlights: The injection orientation and position are studied on a turbine honeycomb tip. The injection pipes are arranged on the cavity bottom at fixed inclined angle. The injection orientation and position both affect the leakage feature. The leakage rate and downstream loss differ with the orientation and position. The heat load on the blade tip and suction surface is improved. Abstract: The effect of the cooling injection orientation and position on the tip leakage flow has been studied numerically in a honeycomb-tip turbine cascade. The injected fluid enters each honeycomb cavity through the bottom pipe at a fixed incident angle. The effect of the relative casing motion with six casing speeds is considered. The Reynolds-averaged Navier-Stokes (RANS) method and k - ω turbulence model were used in the three dimensional computations. Then the leakage mass flow rate and the averaged total pressure loss are evaluated. The static pressure and limiting streamlines on the casing are discussed and the flow direction around the gap are extracted to precisely analyze the leakage feature. Besides, the thermal conditions on the blade tip and suction surface are described by the Nusselt number and adiabatic film cooling effectiveness. Finally, the dimensionless temperature contours and velocity vectors inside the gap are plotted to explore the effect of the injection position. The results indicates that the injection feature mainly depends on the injection orientation and finally determines the aerodynamic and thermodynamic performance.